Antifungal and antibacterial activity of actinomycetes isolated from the sundarbans mangrove forest soil and water from Bay of Bengal - Rahman, Md. Fahad (2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.